Awareness and Its Associated Factors of Obstetrics Fistula among Antenatal Care Attendees in Injibara Town Health Institutions, Awi Zone, North West, Ethiopia, 2019 - Wondu Feyisa Balcha; Azezu Asres Nigussie; Fentahun Yenealem Beyene; Azimeraw Arega Tesfu (Journal of Pregnancy)
Background. Obstetric fistula is abnormal passageway between the vagina and bladder or rectum, and it has the most devastating effects on physical, social, and economic levels and represents a major public health issue of thousands of women, which failed to provide accessible and appropriate intrapartum care for women within a developing country, particularly in Ethiopia. Therefore, we tried to assess the awareness and its associated factors of obstetrics fistula among pregnant mothers attending antenatal care clinics. Methods. A health institutional-based cross-sectional study was employed from March 4 to 29/2019 among 413 pregnant women. Data was collected by a systematic random sampling technique and entered into a computer using Epi data 3.5, edited and analyzed using Statistical Package of Social Sciences 23.0 version. Bivariate and multivariate logistic regression analyses were employed to estimate the crude and adjusted odds ratio with a confidence interval of 95% and p value of less than 0.05 considered statically significant. Result. This study identified that 39.5% with 95% confidence interval (34.6-44.6%) of pregnant women had good awareness about obstetrics fistula. Multivariate logistic regression analysis showed that living in urban [AOR=1.98, 95% CI=1.07−3.69], attending formal education [AOR=2.11, 95% CI=1.06−4.12], having history antenatal care [AOR=3.87, 95% CI=1.60−9.68], and childbirth at health institution [AOR=7.10, 95% CI=2.52−2.02] were significantly associated with awareness of obstetrics fistula. Conclusion and recommendation. This study showed that awareness of obstetrics fistula was low. Residency, education, and occupation of the women, having history of antenatal care and childbirth at health institution was significantly associated with awareness of obstetrics fistula. Still, there is a gap on awareness of obstetrics fistula; therefore, it is good to emphasize on providing information on maternal health care issues, particularly about obstetrics fistula.